Dynamics of the indicators of educational motivation of medical students at different stages of learning - N.V. Mishina; S.I. Ilchenko; A.A. Yefanova (Zaslavsky O.Yu., 2019)
Background. The emergence of new communication and information networks make people to adapt to the new realities of life. The requirements for higher education are changing. The transition to the credit transfer system of education, which provides the formation of students' self-organization skills, focuses on increasing the level of their responsibility, motivates them to develop self-study skills. Objective: the definition and comparison of the orientation of motivation, as well as the determination of the dominant motives for choosing the profession in third- and sixth-year students and interns of the Dnipropetrovsk Medical Academy. Materials and methods. The study involved 168 third-year students, 28 sixth-year students, as well as 15 interns of the Dnipropetrovsk Medical Academy. We have used the test questionnaire of A.O. Rean "Motivation to achieve and avoid failure", as well as A.O. Rean and V.O. Yakunin test for determining the motives of students' learning. The Microsoft Excel 2010 program was used to process the findings. Results. It was revealed that a greater number of students is characterized by the presence of positive motivation in the learning process. At the same time, the number of sixth-year students and interns with a high level of positive motivation is much higher than that of third-year students. It was also found that for a larger number of students, the presence of internal, cognitive motives is characteristic. It should be noted that, depending on the year of study, the prevailing motives for teaching students vary, which may be related to the formation of interest in studies, an understanding of the meaning of learning activities and the importance of this process for the future life of a particular student. Conclusions. Since the successful formation of the professional readiness of young specialists consists not only in identifying the real level of existing motivation, but also in adjusting and controlling the dynamics of changes of the motivational component in the process of their practical training, the results of this study can serve as a basis for further improvement of the educative process and self-development of students, taking into account their individual and personal qualities.